Great white summer [videorecording (DVD)] - Salerno, Aj; Skomal, Greg; Hawthorn-Doyle, Heather (Gravitas Ventures, 2024)
Nature, culture and human life collide as sharks, surfers, scientists and society fight for everything they value. In Great White Summer, a Cape Cod coastal community struggles with increasing threats from a growing shark population, and the bad blood growing in their own community.